Weighted Multilinear Hardy Operators on Herz Type Spaces - Gong, Shuli; Ma, Bolin; Fu, Zun Wei (TheScientificWorld, 2014)
This paper focuses on the bounds of weighted multilinear Hardy operators on the product Herz spaces and the product Morrey-Herz spaces, respectively. We present a sufficient condition on the weight function that guarantees weighted multilinear Hardy operators to be bounded on the product Herz spaces. And the condition is necessary under certain assumptions. Finally, we extend the obtained results to the product Morrey-Herz spaces.